Separation and Recovery of SiC Particles Discharged from Silicon Wafer Production Process - Shibata, Junji; Murayama, Norihiro (Journal of Applied Solution Chemistry and Modeling, 2014)
In the slicing process of silicon wafer from silicon single crystal, it has been the general way to cut silicon by wire saws with the lubricant mixture of silicon carbide, as SiC, particles and wrapping oil. After slicing the silicon single crystal, the waste liquor containing SiC and silicon powders is discharged from the process. The particle sizes of SiC and Si are about 10μm and 1μm, respectively and the weight ratio is about 9:1. The particles discharged from slicing waste liquor become the mixture of SiC and SiO2, when the waste liquor is burned after treating the lubricant oil by a filter press. In terms of the minimization of wastes and environment, it is preferable to separate and recover the valuable SiC from SiO2. In order to solve the problem mentioned above, flotation method can be applied to accomplish the separation of SiC from SiO2. The cationic surfactants of dodecyl-tri-methyl-ammonium chloride (abbreviated as DTMAC hereafter) and tri-methyl-octyl-ammonium chloride (abbreviated as TMOAC hereafter) were used in this study. The adsorption amount of surfactants on SiC and SiO2 particles was measured. The flotation behaviors of SiC and SiO2 were investigated by changing pH, gas flow rate and flotation time in the presence of DTMAC. The purity and yield of SiC were also discussed in the flotation process comprising of roughing, cleaning and scavenging steps. A series of flotation process for SiC gave the purity and yield of 99.7% and 96.7%, respectively.